The immune response to major gastrointestinal cancer surgery and potential implications for adjuvant immunotherapy. (July 2022) - Donlon, Noel E.; Davern, Maria; Hayes, Conall; Power, Robert; Sheppard, Andrew D.; Donohoe, Claire L.; Lysaght, Joanne; Reynolds, John V.
Abstract: The perioperative period theoretically is a critical time of opportunity for the progression of pre-existing tumour micrometastasis. Therefore, the timing of introducing cancer therapies including chemotherapy, radiation therapy and immunotherapies in the postoperative period is important. A thorough exploration of the perioperative immune events at a cellular level in combination with an intricate review of available clinical rials was conducted to extrapolate the effects of oncological surgery on the perioperative immune milieu.This is timely in view of the recently published Checkmate-577 trial which demonstrated significant disease-free survival in carcinoma of the gastroesophageal junction with the use of adjuvant anti-programmed cell deathprotein 1(PD-1) immunotherapy.This review focusing in particular on perioperative immunosuppression, identifies potential modifiable factors, the effects of perioperative conditioning and optimisation, the most recent trials in the curative setting for Gastrointestinal malignancies and the new treatment avenues possible in the context of the combination of immunotherapy and major oncological gastrointestinal surgery. Highlights: Major oncological surgery constitutes an immunosuppressive milieu perioperatively. Th1 to Th2 switch. Therapeutic potential to offset the immunosuppressive tumour microenvironment perioperative with immune checkpoint inhibition. Immunotherapy and conventional therapies may propagate anti-tumour responses.